The cerebral metabolic mechanism of group computer magnanimous therapy based on magnetic resonance spectroscopy: effects on improving magnanimous-enterprising levels of lung cancer patients - Liu, Qianyu; Ma, Qihui; Sun, Qingfeng; Huang, Xuewei (Frontiers in Psychiatry, 2024)
IntroductionThis study aims to evaluate the effects of group computer magnanimous therapy (GCMT) on magnanimous-enterprising levels and brain metabolic changes in patients with advanced lung cancer.MethodsIn this multicenter, randomized controlled trial, 47 participants diagnosed with advanced stage (III or IV) lung cancer were randomly assigned to either the GCMT group (GCMTG, n = 31) or the control group (CTRLG, n = 16). The GCMTG received routine oncotherapy and care along with eight sessions of GCMT over 2 weeks, while the CTRLG received only oncotherapy and routine care. Psychological and brain metabolic changes were assessed using the Enterprising and Magnanimous Questionnaire (EMQ) and proton magnetic resonance spectroscopy (1H-MRS).ResultsAfter 2 weeks, the GCMTG showed significant improvements in the EMQ “total score” and “enterprising” dimensions compared to baseline (p < 0.05), while the CTRLG showed no significant changes. Significant increases in NAA/Cr levels were observed in the right amygdala, and significant decreases in mI/Cr levels were observed in the right cingulate gyrus in the GCMTG. Pearson correlation analysis indicated that changes in Cho/Cr levels in the left amygdala and Glx/Cr levels in the left hippocampus were significantly correlated with improvements in the enterprising dimension.ConclusionsGCMT significantly enhanced enterprising attitudes and induced beneficial changes in brain metabolites among patients with advanced lung cancer. Further research with larger sample sizes is warranted to confirm these results and explore the long-term effects of GCMT.Clinical trial registrationhttps://www.chictr.org.cn/showproj.html?proj=129557, identifier ChiCTR2100053015.